Perancangan Buku Damar Kurung Gresik Dengan Teknik Vector Sebagai Upaya Mengenalkan Kebudayaan Kabupaten Gresik - Fithriyadi, Muhammad Nur; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
The purpose of the design book Timber Brackets Gresik is to introduce the culture of Gresik Regency. Further research is done using qualitative research methods that do interviews, observation, and literature to obtain data used to support the creation of design concepts book Timber Brackets Gresik. The data were analyzed by using multiple stages, namely the reduction of data, data presentation, and conclusion. After analyzing the data, the found a design concept or the keyword